Penerapan Media Pembelajaran Audio Visiual Untuk Meningkatkan Hasil Belajar Biologi Pada Materi Ekosistem Kelas X.2 Di SMA Negeri 1 Meureubo - Syah Mohd Hadiid Thaariq; Dian Kristanti; Tjoet Dewi Balkis Karisma (LPPM Universitas Cipta Mandiri, 2025)
This research aims to improve student learning outcomes in biology subjects, especially in ecosystem material, by using audio-visual learning media. The research was carried out in class X.2 of SMA Negeri I Meureubo. The background to this research is that low student learning outcomes are caused by less interesting learning methods such as the lecture method. It is hoped that audio-visual learning media can facilitate students’ understanding through visualization of abstract ecosystem concepts. This research uses the Classroom Action Research (PTK) method with two cycles, involving planning, implementation, observation and reflection. The results showed that the application of audio visual learning media increased student learning outcomes from 41% in cycle I to 100% in cycle II, with the average student score increasing from 79 to 96. Audio visual learning media was proven to be effective in increasing student understanding and making the learning process is more interactive and interesting.